The Effect Of Intermittent Fasting And Light Physical Activity On Body Weight And Blood Glucose In Overweight Men - Harahap, Huntari; Kusdiyah, Erny; Hasibuan, Mhd Usni Zamzami (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2024)
ABSTRACT Background: Obesity is a global epidemic that can increase metabolic syndrome and insulin resistance risk. Diet modification and light exercise can control metabolism. Intermittent fasting is a time limit for eating, and there are cycles of fasting diets for specific periods. This study aimed to determine the effect of intermittent fasting and light physical activity on body weight and blood glucose in overweight and obese men. Methods: This research method is a Quasi-Experimental study with a Cross-Sectional research design with a sample of 21 men aged 18 to 50 years with BMI > 23 mg/dl and able to participate in the study to completion. Results: The results showed that Alternate Day Fasting and light physical activity can reduce body weight (mean = 84.53) compared to previous body weight (mean = 82.47). There was no difference in blood glucose (Mann Whitney; p> 0.05). Conclusion: Intermittent Fasting Diet can reduce body weight but does not cause changes in blood glucose in overweight and obese men.